Comparative effects of snoring sound between two minimally invasive surgeries in the treatment of snoring: a randomized controlled trial. - Li-Ang Lee; Jen-Fang Yu; Yu-Lun Lo; Ning-Hung Chen; Tuan-Jen Fang; Chung-Guei Huang; Wen-Nuan Cheng; Hsueh-Yu Li (PLoS ONE, 2014)
Minimally invasive surgeries of the soft palate have emerged as a less-invasive treatment for habitual snoring. To date, there is only limited information available comparing the effects of snoring sound between different minimally invasive surgeries in the treatment of habitual snoring.To compare the efficacy of palatal implant and radiofrequency surgery, in the reduction of snoring through subjective evaluation of snoring and objective snoring sound analysis.Thirty patients with habitual snoring due to palatal obstruction (apnea-hypopnea index ≤15, body max index ≤30) were prospectively enrolled and randomized to undergo a single session of palatal implant or temperature-controlled radiofrequency surgery of the soft palate under local anesthesia. Snoring was primarily evaluated by the patient with a 10 cm visual analogue scale (VAS) at baseline and at a 3-month follow-up visit and the change in VAS was the primary outcome. Moreover, life qualities, measured by snore outcomes survey, and full-night snoring sounds, analyzed by a sound analytic program (Snore Map), were also investigated at the same time.Twenty-eight patients completed the study; 14 received palatal implant surgery and 14 underwent radiofrequency surgery. The VAS and snore outcomes survey scores were significantly improved in both groups. However, the good response (postoperative VAS ≤3 or postoperative VAS ≤5 plus snore outcomes survey score ≥60) rate of the palatal implant group was significantly higher than that of the radiofrequency group (79% vs. 29%, P = 0.021). The maximal loudness of low-frequency (40-300 Hz) snores was reduced significantly in the palatal implant group. In addition, the snoring index was significantly reduced in the radiofrequency group.Both palatal implants and a single-stage radiofrequency surgery improve subjective snoring outcomes, but palatal implants have a greater effect on most measures of subjective and objective snoring. Multi-stage radiofrequency surgery was not tested.ClinicalTrials.gov NCT01955083.